Isolation of α-mangostin from mangosteen (Garcinia mangostana L.) peels and evaluation of its inhibitory activity toward α-glucosidase and α-amylase in the combination with acarbose - Van Quang, Ngo; Hong Minh, Nguyen Thi; Mai Phuong, Nguyen Thi (Vietnam Journal of Biotechnology, 2022)
Using the natural agents with inhibitory activity against digestive enzymes α-glucosidase and α-amylase capable of hydrolyzing carbohydrates into glucose to reduce blood glucose levels in the blood is one of the effective strategies to control diabetes, especially type II diabetes. α-Mangostin (AMG) was proven to have strong biological activities, such as antifungal, antibacterial, anti-inflammatory, anti-cancer. However, the evaluation of the antidiabetic activity of this substance through inhibition of starch hydrolytic enzymes activity has not been fully carried out, especially when they are combined with commercial drugs, such as acarbose. In this study, AMG was isolated from the peels of the mangosteen grown in Vietnam using a simple isolation process with two steps: i) fractionation of the material in n-hexane solvent, and ii) chromatography of n-hexane fraction on a silica gel column combined with crystallization. The α-glucosidase inhibitory activity (AGI) and α-amylase inhibitory activity (AAI) of purified AMG alone or in combination with acarbose were then determined spectrophotometrically. The obtained results indicated that AMG had a purity of > 98% by HPLC examination and its chemical structure was confirmed by NMR spectra analysis combined with the reference. The isolated AMG showed good AGI and AAI with IC50 values of 8.25 µg/mL and 24.5 µg/mL, respectively. The AGI increased to 69.4% when AMG (5.0 µg/mL) was combined with acarbose at a concentration of 2.5 µg/mL, while the AAI did not have a clear synergistic effect. Our finding suggests the possibility of using the combination formula to enhance acarbose efficacy in treatment of the disease.